Widdershins - Onions, Oliver, 1873-1961 (Salt Lake City, UT : Project Gutenberg, 2004)
"Widdershins" by Oliver Onions is a novel written in the early 20th century. The story revolves around Paul Oleron, an author who has recently moved into a dilapidated old house, drawn in by its peculiar charm despite its unsettling atmosphere. As he seeks a quieter space to continue his writing, he becomes increasingly aware of the strange occurrences surrounding him, implying a deeper connection between the house and his own creative struggles. The opening of "Widdershins" introduces Oleron as he encounters the old house for the first time, passing the ominous "To Let" signs that suggest its uninhabitable state. After deciding to rent the first floor, he begins to settle in, rekindling memories of his late grandmother's belongings as he decorates. However, as he tries to focus on his writing, distractions from the house's peculiar noises and thoughts of his unfinished novel arise, hinting at a mysterious presence within. These layers of suspense within the domestic setting spark intrigue about Oleron$1 (Bs mental and emotional journey, as he navigates the challenges of inspiration, companionship, and the potential haunting of both his workspace and soul. (This is an automatically generated summary.)s
The beckoning fair one -- Phantas -- Rooum -- Benlian -- Io -- The accident -- The cigarette case -- The rocker -- Hic jacet.
Release date is 2004-11-26
E-text prepared by Suzanne Shell, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Ghost stories, English